Dual-task effects of walking-speed on inhibitory control and decision-making under risk - Carlotta Maiocchi; Marta Milanesi; Nicola Canessa; Stefania Sozzi; Giulia Mattavelli; Antonio Nardone; Claudia Gianelli (Scientific Reports)
Abstract The effect of simultaneously performing two tasks (dual-task effects, DTEs) has been extensively studied, mainly focusing on the combination of cognitive and motor tasks. Given their potentially detrimental impact on real-life activities, the impact of DTEs has been investigated in both healthy individuals and patients. In this Registered Report, we aimed to replicate previous DTEs when a task requiring executive-inhibitory skills is involved while also expanding the evidence on basic facets of decision-making. We recruited 50 healthy young participants who performed a stop-signal task and two gambling tasks (loss-aversion and risk-aversion) while sitting and while walking at three treadmill speeds (normal, slow and fast). We report a significant difference in performance during single-task and dual-task, although with high individual variability. The data show no effect of the walking speed on all the cognitive tasks. Analyses on postural alignments, assessed in the cadence, gait cycle length and stance phase, confirm previous results on cognitive prioritization strategies of healthy individuals. Based on our results, we highlight the need to further investigate prioritization strategies when tasks involving higher cognitive functions are performed along a motor task in healthy individuals and patients with the aim of offering targeted training and rehabilitation protocols. The stage 1 protocol for this Registered Report was accepted in principle on 28/06/22. The protocol, as accepted by the journal, can be found at: https://doi.org/10.17605/OSF.IO/5MWH7 .